-8b+31=-7(2b-7)

Simple and best practice solution for -8b+31=-7(2b-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8b+31=-7(2b-7) equation:


Simplifying
-8b + 31 = -7(2b + -7)

Reorder the terms:
31 + -8b = -7(2b + -7)

Reorder the terms:
31 + -8b = -7(-7 + 2b)
31 + -8b = (-7 * -7 + 2b * -7)
31 + -8b = (49 + -14b)

Solving
31 + -8b = 49 + -14b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '14b' to each side of the equation.
31 + -8b + 14b = 49 + -14b + 14b

Combine like terms: -8b + 14b = 6b
31 + 6b = 49 + -14b + 14b

Combine like terms: -14b + 14b = 0
31 + 6b = 49 + 0
31 + 6b = 49

Add '-31' to each side of the equation.
31 + -31 + 6b = 49 + -31

Combine like terms: 31 + -31 = 0
0 + 6b = 49 + -31
6b = 49 + -31

Combine like terms: 49 + -31 = 18
6b = 18

Divide each side by '6'.
b = 3

Simplifying
b = 3

See similar equations:

| 3(3v-4)=51 | | 1.25(s+72)=250 | | (5u-7)(2+u)=0 | | .4(2-q)=0.2(q+7) | | 3(5)+5x=9 | | 35-x=4x | | y+7/9=8/5 | | Y=5/2x+20 | | x^2-1.375x=7 | | x-35=4x | | (4x-9)/(7x^2+9x) | | -4-(5-3p)= | | x-3/4-2=x-2/3 | | 5.3x+4=4.3x | | 34=5x+16x^2 | | 6x-(-3x+9)=(x-7)-4(9x-9) | | (4x-9)/(7x^2+9) | | 5[x]=45 | | 5n+1=5(n-1) | | 8(k+11)-6k=9 | | 3u+4=22 | | 16x^2+5x=0 | | 7x+21=2x+56 | | 20y^2-15y^3= | | 1/4(x-3)=1/3(x-2) | | f(x)=5-.2x | | c/8+230/8=200 | | 22/1 | | 5r^2-16r+12= | | -5y-9=4y+2 | | 3k+34=4(6+3k)+1 | | -6-(-2n)=3-6+5 |

Equations solver categories